Implementasi Kewarisan Adat di Sumatera dalam Tinjauan Maqashid Syari’ah dan Ketatanegaraan Indonesia - Mohammad Ridwan (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2023)
In the adat of the people of Sumatra, the majority of the people are Muslims, therefore automatically all aspects of their life must be based on Islam. Thus, from the implementation of inheritance, the community should use a system derived from Islamic law as their religion and belief. The method used in this study is a descriptive method which is carried out by observing, understanding and describing an event with a complete analysis, in this case data on the customary inheritance system in Sumatra. Thus it can be concluded that: 1) the Simalungun people continue to carry out their customary law to complete the distribution of inheritance, even though the majority of them have embraced Islam; 2) Implementation of inheritance in Minangkabau custom is divided into two kinds of ways and there are also two kinds of inheritance, namely high inheritance inherited from the female lineage; and lower inheritance which in its implementation is in accordance with Islamic inheritance law; 3) The Basemah indigenous people still adhere to the concept of patrilineal genealogy. This system is one in which the eldest son, who is often the male, becomes the sole owner of the assets of his parents and predecessors and does not transfer them to heirs.